Colliding localized, lumpy holographic shocks with a granular nuclear structure - Sebastian Waeber; Laurence G. Yaffe (Journal of High Energy Physics, 2023)
Abstract We apply a recent and simple technique which speeds up the calculation of localized collisions in holography to study more realistic models of the pre-hydrodynamic phase of heavy ion collisions using gauge/gravity duality. Our initial data reflects the lumpy nuclear structure of real heavy ions and our projectiles’ aspect ratio mimics the Lorentz contraction of nuclei during RHIC collisions. At the hydrodynamization time of the central region of the quark gluon plasma developed during the collision, we find that most of the system’s vorticity is located well outside the hydrodynamized part of the plasma. Only the relativistic corrections to the thermal vorticity within the hydrodynamized region are non-negligible. We compare the transverse flow shortly after the collision with previous results which did not use granular initial conditions and determine the proper energy density and fluid velocity in the hydrodynamized subregion of the plasma.